Child labour in Pakistan: Addressing supply and demand side labour market dynamics. (June 2017) - Fatima, Ambreen
This article uses empirical evidence, based on labour market indicators, to analyse the factors influencing the incidence of child labour in Pakistan, from both supply and demand sides. The level of demand for child labour is shown to be linked mainly to adult wage levels, the adult unemployment rate in an area, and the size of the informal and agriculture sectors. The supply of child labour is seen to be positively linked to the proportion of adult unemployment in the household. Unlike previous studies, the article analyses both demand and supply side factors in a context of poverty and takes account of the co-existence of formal and informal labour markets. Furthermore, to generalise the issue for a longer span of time (which previous studies fail to do), it adopts the methodology of a pseudo-panel approach based on that proposed by Deaton. This approach makes it possible to pinpoint more accurately the factors, and their interaction, that need to be considered in any effective policy approach to the issue of child labour. To prevent unintended consequences, a multi-faceted development approach is required.